Lightweight Concrete Bricks Produced from Industrial and Agricultural Solid Waste - Ling, H.; Teo, Delsye Ching Lee (IEEE, 2011)
The continuous extraction of natural nonrenewable resources such as lime and natural aggregates for the production of concrete, the introduction of sustainable development to overcome the issues of natural resource depletion has been gaining increased attention. The main objective of this research is to address the potential use of both agricultural and industrial wastes namely Rice Husk Ash (RHA) and Expanded Polystyrene (EPS) respectively as raw material for the production of 'Green' lightweight concrete bricks. RHA was used as partial cement replacement, while the EPS was used as partial aggregate replacement in the mixes. Five different mix proportions were prepared. Sample A acts as the control sample (without RHA) and has a Cement: Sand: EPS ratio of 1.0: 1.5 : 1.5, while samples B, C, D and E have RHA replacements of 5%, 10%, 15% and 20% respectively. The samples were tested for fresh concrete namely slump, fresh concrete density and air content while the hardened concrete properties tested were sorptivity, compressive strength and thermal conductivity. It was determined that EPS RHA concrete brick gives promising results